2016
DOI: 10.1039/c6cp03064e
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of ternary Co3O4/carbon coated TiO2 hybrid nanocomposites for asymmetric supercapacitors

Abstract: Recently, attention has been focused on the synthesis and application of nanocomposites for supercapacitors, which can have superior electrochemical performance than single structured materials. Here, we report a carbon-coated TiO2/Co3O4 ternary hybrid nanocomposite (TiO2@C/Co) electrode for supercapacitors. A carbon layer was directly introduced onto the TiO2 surface via thermal vapor deposition. The carbon layer provides anchoring sites for the deposition of Co3O4, which was introduced onto the carbon-coated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…With respect to S 2p spectrum, the peak at about 163.1 eV (S 2p1/2) is assigned to the binding energy of metal-sulfur bond (including NiÀS or CoÀS bond), while the component at 161.8 eV (2p 3/2) is the feature of the sulfur ions in low coordination at the surface. Aforementioned results accord with the previous reported data of NiCo 2 S 4 , [29,30] indicating that the surface ingredient of the hybrid product is composed of Co 3 + /Co 2 + , Ni 3 + /Ni 2 + , S 2À and proving the existance of NiCo 2 S 4 .…”
Section: The Synthesis and Characterization Of Materialssupporting
confidence: 91%
See 1 more Smart Citation
“…With respect to S 2p spectrum, the peak at about 163.1 eV (S 2p1/2) is assigned to the binding energy of metal-sulfur bond (including NiÀS or CoÀS bond), while the component at 161.8 eV (2p 3/2) is the feature of the sulfur ions in low coordination at the surface. Aforementioned results accord with the previous reported data of NiCo 2 S 4 , [29,30] indicating that the surface ingredient of the hybrid product is composed of Co 3 + /Co 2 + , Ni 3 + /Ni 2 + , S 2À and proving the existance of NiCo 2 S 4 .…”
Section: The Synthesis and Characterization Of Materialssupporting
confidence: 91%
“…[23] Therefore, lots of supercapacitive materials are based on various morphology of Co 3 O 4 . [24][25][26][27][28][29][30][31][32][33] For example, Zheng et al have synthesized mesoporous Co 3 O 4 nanowires as efficient water oxidation electrocatalysts and supercapacitor electrodes. [31] Cheng et al has reported Co 3 O 4 @MnO 2 hierarchical nanoneedle arrays applied to energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with those in previous studies (Table 1), the specic capacitance and cycling performance at high current density is notably improved. [48][49][50][51][52][55][56][57] The asymmetric supercapacitor device was further assembled with the as-prepared Co 3 O 4 /Ni and active carbon (Co 3 O 4 / Ni//AC). The electrochemical performance was evaluated and the results are shown in Fig.…”
Section: Electrochemical Performancementioning
confidence: 99%
“…For example, one-dimensional Co 3 O 4 nanostructures showed preferable electrochemical properties in previous studies. [48][49][50][51][52] To date, large attention has been drawn towards using different methods for the synthesis of one dimensional Co 3 O 4 nanostructures with excellent electrochemical properties (e.g. hydro-thermal method).…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice application, single Co 3 O 4 materials possess poor electrode stability and low cyclic stability. 23,24 Therefore, one has designed various hybrid structures to use their synergetic effect to improve the electrochemical properties of Co 3 O 4 nanomaterials. Du et al successfully synthesized porous Co 3 O 4 nanosheets@RGo nanocomposite using a simple hydrothermal process.…”
Section: Introductionmentioning
confidence: 99%